I Samuel a new translation with introduction, notes and commentary - McCarter, Peter Kyle, Jr. 1945- (Garden City, NY Doubleday, 1980)
Includes bibliographical references and indexes.
Keywords: Bible O.T. Samuel 1st -- commentaries